The application of electrocoagulation process for treatment of the red mud dam wastewater from Bayer's process - Kobya, M.; Oncel, M. S.; Demirbas, E.; Sik, E.; Akyol, A.; İnce, Mahir (Elsevier Sci Ltd, 2014)
In this study, the effectiveness of electrocoagulation (EC) process using iron sacrificial electrodes for the removal of waste red mud slurry (RMW) from the aluminium industry was investigated. Effects of current density (10-75 A/m(2)), pH (6-12) and operating time (0-45 min) on the removal of RMW were evaluated to obtain optimum operating conditions. The dissolved metal concentrations of residues in the wastewater at pH 5-12 were determined. The removal efficiencies of V, Si, Al, As, Mo and Ga present in the wastewater at pH 8, current density of 50 A/m(2) and operating time of 45 min were measured as 97.68%, 82.65%, 98.22%, 99.44%, 99.69% and 99.95% in the EC process, respectively. The sludge produced after the EC process was characterized with scanning electron microscope. The amount of sludge and operating cost at the optimum operating conditions were calculated as 2.138 kg/m(3) and 0.813 s/m(3). (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Red mud; Electrocoagulation; Iron electrode; Operating cost; Sludge analysis